Efektivitas Program Keluarga Sehat Terhadap Kemandirian Keluarga Dalam Mengatasi Masalah Sanitasi Lingkungan Di Kelurahan Sempaja Selatan Kecamatan Samarinda Utara Kota Samarinda - Johan, Herni; Yusuf, Nuuva; Nurlisa, Siti (Bunda Edu-Midwifery Journal (BEMJ), 2019)
Research "Effectiveness of Healthy Family Programs Against Family Independence in Overcoming the Problem of Environmental Sanitation". This is a research development program on Healthy Indonesia Against Family Independence (PIS-PK) in an effort to improve the quality of human life, especially Indonesia. Developed countries one of the supporting indicators is the level of human independence or good family. Where the independence of the family is known 45% of Indonesia's population lives in an environment that is still not good for health environmental sanitation and this condition increase various health risks so that it impacts on the efficiency of health costs which are a burden on the government and society. The long-term goal to be achieved is to find out the effectiveness of a healthy family program on family independence in addressing environmental sanitation problems so that the specific target of implementing the Healthy Indonesia Program on family independence can improve healthy living standards in overcoming environmental sanitation problems family scope. The method used in this study with the Pre Experiment approach design the one group pretest posttest. The results showed that the healthy Indonesia program could increase family independence in overcoming environmental sanitation problems.